Detection of android material components in application usage videos (2017)
This is a project capable of detecting Android Material components in applications usage videos (videos that anyone can easily take from its phone in a short time and almost none effort). The project could help in the life cycle of an application, from the development through the maintenance and testing, improving the final results experience by the user. This software that can detect some Android Material components, could be a foundation for detecting the activities to which the components belong, and the flow of activities that would allow the detection of usage patterns in an application